Response of Four Species of Tropical Timber Seedlings to Urea and Folivert Fertilisers in Nursery. - Andrew, Egbe Enow; Limbi, Tata Blessing; Ayamoh, Enow Elsie (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
This study explores the effects of different levels of urea and folivert (composite fertilizer) on seedlings growth and chlorophyll concentration of Albizia zygia, Blighia welwitschii, Lophira alata and Pterocarpus soyauxii. The rate of fertilizer application per 5.87kg pot with topsoil was 3, 6, and 9g of both urea and composite fertilizer and a control (top soil only) and it was a complete randomized design. Results indicated that plants treated with 3g of urea produced the highest number of leaves in Albizia zygia seedlings only while 9g of composite fertilizer had the best growth performance in all the other growth variables. Albizia zygia and Blighia welwitschii, seedlings had the best results in soil treated with 6g of composite fertilizer, while Lophira alata and Pterocarpus soyauxii seedlings showed best growth in soils treated with 9g of composite fertilizers for all other parameters. Seedlings of species supplied with 9g of urea gave poorest growth performance. Low root/shoot ratios were obtained for all seedlings except for those of Albizia zygia treated with 6 and 9g of urea that had root/shoot ratios greater than 1.0. The effect of fertilizers on chlorophyll concentration was significantly different only for L. alata (P=0.05). This study therefore brings to light the need to fertilize timber tree seedlings in order to improve on their early growth performances in the field and high doses of nitrogen should be discourage.